Europe’s lost landscape sculptors: Today’s potential range of the extinct elephant Palaeoloxodon antiquus - Franka Gaiser; Charlotte Müller; Paula Phan; Gregor Mathes; Manuel J. Steinbauer (Frontiers of Biogeography)
The straight-tusked elephant (Palaeoloxodon antiquus) was amongst the largest herbivores once engineering the European landscape on a continental scale. In combination with the glacial-interglacial cycles of the Pleistocene, the species was an integral part of the control regimes that shaped European flora and fauna. With the human-facilitated extinction of the straight-tusked elephant, these landscape-forming processes were lost during the last Glacial-Interglacial cycle. Given today’s climate, could straight-tusked elephants still be part of modern ecosystems in Europe? And if yes, where? Answers to these questions can support nature conservation in preserving species and ecosystems historically adapted to these lost control regimes. We reconstructed the realised niche of the straight-tusked elephant by allocating a novel compilation of fossil occurrences to either cold or warm stages, based on their assignment to Marine Isotope Stages. Further, we quantified the past potential distribution of the straight-tusked elephant since its extinction and its current potential distribution given the modern climate. Results show that the elephant could have persisted in the Mediterranean Basin until today and that modern climate across Central and Western Europe, excluding the Alps, as well as in the Mediterranean, is highly suitable for its occurrence. Our results show that, without human-induced extinctions, European fauna would comprise extinct megafauna, acting as ecosystem engineers on a continental scale. Local rewilding initiatives aim at restoring these lost processes, but potentially cannot achieve lasting ecological effects on comparable scales. Highlights The current European climate would still be suitable for the extinct straight-tusked elephant (Palaeoloxodon antiquus). The straight-tusked elephant could have persisted during the last Glacial-Interglacial cycle, considering past climate. Conserving the ecosystems shaped by the top-down ecosystem functions executed by the straight-tusked elephant in Europe may be especially promising in regions where the elephant could still exist today. Using reference cold and warm stages, based on Marine Isotope Stages in a Species Distribution Modelling framework, is a promising attempt to overcome dating uncertainties inhibiting more specific niche reconstructions of extinct species.